Recent Developments in Kinetic Methods for Trace Constituents - PRASAD, SURENDRA (Asian Journal of Chemistry, 2010)
"Kinetic Method of Analysis" is a newly growing field in the area of analytical chemistry. During the past decade considerable efforts have been directed towards developing increasingly sensitive methods for the determination of trace constituents. Because of their high sensitivity, kinetic-catalytic methods have been recognized as offering a valuable approach to trace analysis. Many methods have been reported for kinetic determination of inorganic species like mercury, copper and nitrite, and also a few for organic species, based on their catalytic effect on ligand substitution or oxidation reactions. This micro-review covers in brief the salient features of the methodology called "Kinetic Methods of Analysis" as applied to trace determination of various species.